Increasing efficiency of Ti-alloy machining by cryogenic cooling and using ethanol in MRF. (August 2017) - Krishnamurthy, G.; Bhowmick, S.; Altenhof, W.; Alpas, A.T.
Highlights: Improvement in machinability of Ti-alloys by the use of liquid nitrogen and ethanol blended metal removal fluid as coolant was studied. Serrated chip formation mechanism under different environments was observed through in situ machining experiments. Characteristic differences in the chips obtained from dry and cryogenic machining conditions were quantified and studied using optical microscopy techniques. Cryogenic cooling promoted fracture between chip segments due to decrease in toughness of Ti at low temperatures. Surface passivation by OH groups from ethanol to the carbon surfaces of the cutting tool decreased adhesion of Ti and led to improved surface finish. Abstract: Generation of high localized cutting zone temperatures leading to dissolution wear hinders machinability of titanium alloys using uncoated carbide tools. In addition, the thermo-plastic instability exhibited by titanium alloys promotes serrated chip formation that causes fluctuations in the cutting forces leading to chatter and severe flank wear. This work considers two methods to mitigate these problems during cutting of Ti-6Al-4V, namely, cryogenic machining and the use of ethanol blended metal removal fluids (MRF). Cryogenic machining decreased the cutting force and surface roughness compared to dry machining under the ambient conditions. The decrease in the fracture energy of Ti-6Al-4V as measured by Charpy impact tests was the likely reason for the predominance of brittle type fracture leading to formation of shorter chip segments during cryogenic machining. The use of ethanol blended MRF reduced the cutting force by over 65% compared to dry machining. Alternatively the use of ethanol blended MRF further reduced the cutting force by over 65% compared to dry machining. The use of ethanol blended MRF resulted in adsorption of OH groups from ethanol to carbon surfaces of the cutting tool resulting in negligible adhesion to the cutting tool.